Mind the Gap: An Annotated Overview of Datasets in the Study of Institutions and Conflict in Divided Societies - Nadine Ansorg; Matthias Basedau; Felix Haass; Julia Strasheim (German Institute of Global and Area Studies (GIGA), 2013)
This paper engages in a systematic overview of the existing datasets on institutions, conflict and peace, as well as divisions and diversity. This overview indicates that an enormous amount of data is unevenly distributed across different issue areas. There is a lack of data capturing specific sets of political institutions (e.g., centripetalism), dynamic changes in a country's relational demographics across identity groups, the ethnicization of political institutions (especially in the security sector), and security sector reform. Many datasets suffer from missing data and an alarming dearth of transparency. Our paper concludes with suggestions for yet unexplored research questions and avenues for further data collection.
Keywords: 300